Utilization of Information and Communication Technology (ICT) Resources - Gelacio, Mary Jane; Comighud, Sheena Mae (IJRDO- Journal of Educational Research, 2020)
This research used the descriptive method to determine the level of utilization of Information and Communication Technology (ICT) Resources in District 4 Public Elementary Schools of Bayawan City Division, Negros Oriental, Philippines for SY 2019-2020. The quantitative data were gathered from 73 research respondents comprised of school heads, ICT Coordinators, and teachers. Also, the researcher conducted a survey questionnaire. Descriptive method was used in this study. The statistical tools used in the analysis of the data were percentage, mean, and weighted mean. The study found out that the level of utilization of Information and Communication Technology (ICT) Resources in the School System was “high” in terms of the following aspects: (a) equipment; (b) facilities; and (c) seminar and training activities. However, the difference in the level of utilization of Information and Communication Technology (ICT) Resources in the School System in the aforementioned areas are not significant according to variables of age, civil status, average family income, and highest educational attainment.